OUTCOME OF LOW TIDAL VOLUME PLUS HIGH PEEP VERSUS CONVENTIONAL VENTILATION IN OBESE PATIENTS UNDER GENERAL ANESTHESIA - Dr. Irfan Hussain Dar; Dr. Mehnaz Syed (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Obesity is a major global health concern associated with altered respiratory mechanics, increased airway resistance, and reduced lung compliance. These changes increase the risk of postoperative pulmonary complications (PPCs) in obese patients undergoing general anesthesia. Optimizing intraoperative ventilation strategies is critical to minimize lung injury and improve postoperative outcomes.Aim: To compare the outcomes of low tidal volume (V_T) ventilation combined with high positive end-expiratory pressure (PEEP) versus conventional ventilation in obese patients undergoing elective surgery under general anesthesia.Methods: This prospective randomized controlled study was conducted at the Department of Anesthesiology and Surgical ICU, Sher-e-Kashmir Institute of Medical Sciences (SKIMS), Soura, from January 2022 to December 2024. A total of 120 adult obese patients (BMI ≥30 kg/m²) scheduled for elective abdominal or laparoscopic surgery were enrolled. Patients were randomized into two groups: Group A (n=60) received low V_T (6–8 ml/kg predicted body weight) plus high PEEP (10–12 cm H2O), and Group B (n=60) received conventional ventilation (10–12 ml/kg tidal volume, PEEP 4–6 cm H₂O). Primary outcomes included incidence of PPCs within 48 hours. Secondary outcomes were intraoperative oxygenation (PaO2/FiO2 ratio), peak and plateau airway pressures, hemodynamic stability, and duration of ICU stay. Data were analyzed using Student’s t-test and Chi-square test; p<0.05 was considered significant. Results: Both groups were comparable in demographic and surgical characteristics. Group A demonstrated significantly lower peak (22 ± 3 vs 28 ± 4 cm H2O, p<0.001) and plateau pressures (18 ± 2 vs 24 ± 3 cm H2O, p<0.001). Postoperative oxygenation was superior in Group A at 1 hour (320 ± 25 vs 290 ± 30, p<0.001) and 6 hours (330 ± 28 vs 295 ± 35, p<0.001) post-extubation. The incidence of PPCs, including hypoxemia (10% vs 23.3%, p=0.04), atelectasis (8.3% vs 21.6%, p=0.03), and need for supplemental oxygen (13.3% vs 30%, p=0.02), was lower in Group A. Hemodynamic parameters were comparable between groups. Conclusion: Low tidal volume ventilation combined with high PEEP improves intraoperative oxygenation, reduces peak and plateau airway pressures, and decreases the incidence of postoperative pulmonary complications in obese patients undergoing general anesthesia. This strategy provides safe and effective lung-protective ventilation, supporting its use as the preferred approach in this high-risk population.